Present state of microchip electrophoresis: State of the art and routine applications - Castro, Eric R.; Manz, Andreas (ELSEVIER SCIENCE BV, 2015)
Microchip electrophoresis (MCE) was one of the earliest applications of the micro-total analysis system (mu-TAS) concept, whose aim is to reduce analysis time and reagent and sample consumption while increasing throughput and portability by miniaturizing analytical laboratory procedures onto a microfluidic chip. More than two decades on, electrophoresis remains the most common separation technique used in microfluidic applications. MCE-based instruments have had some commercial success and have found application in many disciplines. This review will consider the present state of MCE including recent advances in technology and both novel and routine applications in the laboratory. We will also attempt to assess the impact of MCE in the scientific community and its prospects for the future. (C) 2014 Elsevier B.V. All rights reserved.